Relationship Among the State, the Market and the Civil Society in the Case of Privatization of PT Semen Gresik Tbk - Achmad Habibullah (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2010)
Unlike other previous researches on privatization, this research is a critical study with a combination of nonmainstream approaches by a qualitative approach through a disconstructive discourse analysis that elaborates a sharp critique of the structural and NeoMarxist theory on developmentalism within the relationships of the state, the market and the civil society. Results show that in the case of privatization policy of PT Semen Gresik Tbk, interrelationships between the state and the market is dualistic; in certain periods the state enables the market, in other times it constrains the market's opportunity. Akin to the dualistic and domineering nature of economicpolitical structure, interrelationships of the state and the market is asymmetrical, in which the state dominates the civil society, while that of the market and the civil society is asymmetrical, in which the market dominates the civil society. To balance the roles of the state, the market, and the civil society, an intervention by a democratic administration in a symmetrical relationship is needed for the civil society's interests. This research recommends the necessity for the state to put an end to multidimensional crisis by nationalizing assets, for example by buying back the shares of PT Semen Gresik Tbk that were relinquished to foreign investors.